Analysis of Curriculum Planning Management in Producing Qualifications for Graduates of Arabic Departments in Indonesia - Oktavera, Hasnil; Ritonga, Apri Wardana; Islamy, M. Fadil Akbar; Romadhon, Ilham F; Ernawati, Ernawati (Mayada: al-Multaqa al-Ilmy al-Alamy lil-Dirasat al-Arabiyah; Vol 1 No 1 (2023): مجموعة البحوث - الملتقى العلمي العالمي للدراسات العربية, 2024)
يهدف هذا البحث إلى تحليل استراتيجية إدارة تخطيط المناهج المعتمدة على MBKM (حرية التعلم للجامعة الحرة) في قسم تعليم اللغة العربية في إندونيسيا لإنتاج مؤهلات الخريجين تلبي احتياجات المجتمع ومتطلبات العمل من خلال الاستطلاعات عبر الإنترنت. تظهر نتائج هذا البحث أن أقسام اللغة العربية في إندونيسيا قامت بمراجعة منهج KKNI وخططت لمنهج قائم على MBKM باستخدام الإجراءات القياسية. هناك تحديات تواجه التخطيط للمنهج القائم على MBKM : أ) ليس بعد التعاون الأمثل في الشراكة مع الصناعات، ب) لا يزال نظام ضمان الجودة يُدار من قبل وكالة ضمان الجودة (LPM) ، ج) نظام ميزانية الصندوق لبرنامج MBKM مع عدم وضوح اللوائح، د) التنشئة الاجتماعية الأقل فعالية وتجذرًا، و هـ) زيادة كفاءة المحاضر. العديد من الفرص: أ) تعلم اللغة العربية على أساس تكنولوجيا المعلومات ومتكامل مع العلوم متعددة التخصصات، ب) الكثير من الخبرة التعليمية للطلاب، ج) التطوير الأمثل للكفاءات الرئيسية لبرنامج الدراسة، د) احتياجات معلمي اللغة العربية و زيادة المعلمين. This research aims to analyze the curriculum planning management strategy based on Merdeka Belajar Kampus Merdeka (MBKM) in the Arabic Language Education Study Program in Indonesia in producing graduate qualifications that meet community needs and job demands through online surveys. The results of this research show that the Arabic Departments in Indonesia have reviewed the KKNI curriculum and planned an MBKM-based curriculum using standard procedures. There are challenges faced in planning an MBKM-based curriculum: a) not yet optimal partnership collaboration with industries, b) the quality assurance system is still managed by the Quality Assurance Institute (LPM), c) the fund budgeting system MBKM program with unclear regulations, d) socialization that is less effective and rooted, and e) increasing lecturer competency. Several opportunities: a) Arabic language learning based on information technology and integrated with multidisciplinary science, b) quite a lot of student learning experience, c) optimal development of the main competencies of the Study Program, d) the needs of Arabic language teachers and educators increase .